Sex differences in age-related cardiovascular mortality. - Tomi S Mikkola; Mika Gissler; Marko Merikukka; Pauliina Tuomikoski; Olavi Ylikorkala (PLoS ONE)
Introduction Sex-related physiological differences result in different expressions of diseases for men and women. Data are contradicting regarding the increase in the female risk for cardiovascular disease (CVD) at mid-life. Thus, we studied possible sex differences in age-adjusted mortality for CVD and non-vascular diseases stratifying our findings by specific age groups. Methods Over one million deaths (1 080 910) reported to the Finnish nationwide Causes of Death Register in 1986-2009 were analyzed. A total of 247 942 male deaths and 278 752 female deaths were of CVD origin, the remaining deaths were non-vascular. The annual mortality rates were calculated per 100 000 mid-year population, separately for men and women in 5-year age categories. Results The age-standardized risk of death from CVD was 80% higher for men (442/100 000) than for women (246/100 000). After age 45-54 the male CVD mortality rate elevated parallel to the non-vascular mortality, whereas in women the CVD mortality elevated considerably more rapidly than the non-vascular mortality from age 60 years onwards. Conclusions Heart disease mortality in men accelerates at a relatively young age, but in women the risk shows a steep increase at approximately 60 years of age. These data emphasize the need to identify and prevent risk factors for CVD, especially in women in their mid-life years.